2013
DOI: 10.1093/cid/cit246
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Weight, Efavirenz Exposure, and Virologic Suppression in HIV-Infected Patients on Rifampin-Based Tuberculosis Treatment in the AIDS Clinical Trials Group A5221 STRIDE Study

Abstract: EFV and RIF-based tuberculosis therapy coadministration was associated with a trend toward higher, not lower, EFV Cmin compared to EFV alone. Patients weighing ≥60 kg had lower median EFV Cmin versus those <60 kg, but there was no association of higher weight with reduced virologic suppression. These data do not support weight-based dosing of EFV with RIF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
3
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 31 publications
4
66
3
2
Order By: Relevance
“…In contrast to the present data showing more marked changes in exposure, the impact of rifampin-based anti-TB drugs on efavirenz exposure in HIV/TB co-infected patients is either very small (<27% in exposure to no effect) or paradoxically increased efavirenz exposure [2830,41,42]. More importantly, rifampin–efavirenz interactions have no meaningful effect on clinical outcomes of efavirenz [4345].…”
Section: Discussioncontrasting
confidence: 87%
“…In contrast to the present data showing more marked changes in exposure, the impact of rifampin-based anti-TB drugs on efavirenz exposure in HIV/TB co-infected patients is either very small (<27% in exposure to no effect) or paradoxically increased efavirenz exposure [2830,41,42]. More importantly, rifampin–efavirenz interactions have no meaningful effect on clinical outcomes of efavirenz [4345].…”
Section: Discussioncontrasting
confidence: 87%
“…36 A recent pharmacokinetic evaluation of the STRIDE study found that co-administration of efavirenz and rifampin was associated with a trend towards higher, rather than lower, efavirenz C min compared to efavirenz alone. 37 Those weighing ≥60 kg had lower efavirenz C min than those < 60 kg, but did not have lower viral suppression rates.…”
Section: Diagnosis Of Active Tuberculosismentioning
confidence: 91%
“…2,3,18,20 However, a wide degree of interindividual variability in EFV plasma concentrations has been observed, thus making EFV weight-based dosing somewhat unreliable. 21,22 Efavirenz is mainly metabolized through hepatic CYP450 CYP3A4 and 2B6, and recent studies have shown that some ethnicities may be predisposed to slow-metabolizing genetic polymorphisms of CYP2B6 and may not require the dose increase. 2,23 Furthermore, EFV 800 mg daily has not been consistently shown to result in superior virologic suppression and increased concentrations have been associated with central nervous system toxicities.…”
Section: Discussionmentioning
confidence: 99%